Long-Dose Intensive Therapy Is Necessary for Strong, Clinically Significant, Upper Limb Functional Gains and Retained Gains in Severe/Moderate Chronic Stroke. (July 2019) - Daly, Janis J.; McCabe, Jessica P.; Holcomb, John; Monkiewicz, Michelle; Gansen, Jennifer; Pundik, Svetlana
Background . Effective treatment methods are needed for moderate/severely impairment chronic stroke. Objective . The questions were the following: (1) Is there need for long-dose therapy or is there a mid-treatment plateau? (2) Are the observed gains from the prior-studied protocol retained after treatment? Methods . Single-blind, stratified/randomized design, with 3 applied technology treatment groups, combined with motor learning, for long-duration treatment (300 hours of treatment). Measures were Arm Motor Ability Test time and coordination-function (AMAT-T, AMAT-F, respectively), acquired pre-/posttreatment and 3-month follow-up (3moF/U); Fugl-Meyer (FM), acquired similarly with addition of mid-treatment. Findings . There was no group difference in treatment response ( P ≥ .16), therefore data were combined for remaining analyses (n = 31; except for FM pre/mid/post, n = 36). Pre-to-Mid-treatment and Mid-to-Posttreatment gains of FM were statistically and clinically significant ( P < .0001; 4.7 points and P < .001; 5.1 points, respectively), indicating no plateau at 150 hours and benefit of second half of treatment. From baseline to 3moF/U: (1) FM gains were twice the clinically significant benchmark, (2) AMAT-F gains were greater than clinically significant benchmark, and (3) there was statistically significant improvement in FM ( P < .0001); AMAT-F ( P < .0001); AMAT-T ( P < .0001). These gains indicate retained clinically and statistically significant gains at 3moFU. From posttreatment to 3moF/U, gains on FM were maintained. There were statistically significant gains in AMAT-F ( P = .0379) and AMAT-T P = .003.